Training need assessment of mushroom growers and constraints: A study in Nainital district of Uttarakhand - Akansha Joshi; Sharma Kandpal, Arpita; Mishra, S.K. (Mushroom Research, 2022)
Mushroom farming is one of the most potent sources of subsidiary income generation for small and landless farmers. The study was conducted in Haldwani and Bhimtal block of Nainital district, Uttarakhand, India. Three villages viz., Bhasani, Gaulaparao and Saungaun were selected randomly. A sample of 120 respondents was selected through purposive sampling method. Data was collected through structured interview schedule. Results revealed that the mushroom growers belonged to middle age group, major proportion of the respondents were educated upto middle school, had joint family and majority of the farmers have medium mushroom farming experience. More than half of the sample population relied on fellow farmers for information and updates regarding agriculture and related topics. Mushroom growers perceived lack of infrastructure as major constraint. Majority of respondents required training on marketing strategies. Results indicated that mushroom farming experience, information seeking behaviour and income through mushroom cultivation were significantly related to training needs of mushroom growers.